Secondary electron emissive thin film fabricated by atomic layer deposition. (October 2019) - Lin, Yanjian; Gu, Yunting; Yan, Baojun; Liu, Shulin; Wen, Kaile; Wang, Yuman; Heng, Yuekun
Abstract: The secondary electron emissive alumina thin film was fabricated by atomic layer deposition (ALD). The film thickness, structure and composition were characterized by Spectroscopic Ellipsometry (SE), X-ray Diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), respectively. The secondary electron yield ( σ ) of the sample was measured by pulsed electron beam method and the influences of primary electron energy and primary electron angle on the σ have been investigated.